2007
DOI: 10.1111/j.1447-0756.2007.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, endocrine and ultrasonographic features of polycystic ovary syndrome in Thai women

Abstract: The prevalence and clinical presentations of Thai women with PCOS were similar to those in other reports. However, hirsutism, elevated testosterone level and acanthosis nigricans were uncommon in our population. Serum androstenedione was a more sensitive indicator of hyperandrogenemia than total testosterone. Further research is needed to clarify whether there is an ethnic difference in endocrine profiles and risks of metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 19 publications
(23 reference statements)
0
16
2
2
Order By: Relevance
“…Our result implied that biochemical hyperandrogenism consistently presented, while clinical hyperandrogenism varied among different PCOS populations. Compared with another study from Thailand reported by Vutayavanich et al ., our patients had lower prevalence of clinical hyperandrogenism (48.6% vs 61.3%) but higher prevalence of biochemical hyperandrogenism (81.1% vs 37.1%) . The differences between Vutayavanich et al .…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Our result implied that biochemical hyperandrogenism consistently presented, while clinical hyperandrogenism varied among different PCOS populations. Compared with another study from Thailand reported by Vutayavanich et al ., our patients had lower prevalence of clinical hyperandrogenism (48.6% vs 61.3%) but higher prevalence of biochemical hyperandrogenism (81.1% vs 37.1%) . The differences between Vutayavanich et al .…”
Section: Discussioncontrasting
confidence: 47%
“…Polycystic ovary syndrome (PCOS) is a common endocrine disorder in reproductive-aged Thai women with a prevalence of 5-7%. 1 The diagnosis is based on the 2003 Revised Rotterdam criteria which focuses on history of menstruation, clinical or biochemical hyperandrogenism, and ultrasonographic features of the ovaries. 2 PCOS is a heterogeneous disorder of unexplained hyperandrogenism and chronic anovulation.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of this trial is that we did not report androstenedione as the marker of hyperandrogenemia. A previous study in Thai PCOS women showed minority of this population had high level of androstenedione …”
Section: Discussionmentioning
confidence: 68%
“…A previous study in Thai PCOS women showed minority of this population had high level of androstenedione. 33 An mFG score of 6-8 is generally used to define hirsutism. 19 In our population, we found that the mFG score of 8 was the best cut-off point to predict hyperan drogenemia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among mixed ethnic groups in the United States have included small numbers of Asian subjects and lacked information regarding their geographic origins . East Asians generally have lower rates of hirsutism and a higher prevalence of metabolic syndrome compared to Caucasian, Hispanic and African American patients . Asia is a massive continent with ethnic heterogeneity, and therefore each group must be studied separately in order to have reliable information regarding phenotypic manifestations of PCOS.…”
Section: Introductionmentioning
confidence: 99%